(untitled) (TAMADDUN NURI JURNALI, 2025)
This article analyzes aphorisms from a linguistic and stylistic perspective, examining their expression in poetic, prosaic, and metaphorical forms. Aphorisms are short yet deeply meaningful expressions, and their stylistic analysis helps to explore the artistic and expressive capabilities of language. The study identifies that poetic aphorisms are characterized by rhyme and rhythm, prosaic aphorisms by fluency and logical structure, and metaphorical aphorisms by figurative expression and deep layers of meaning.